The Anglophone Crisis in Cameroon: A Geopolitical Analysis - Ekah, Ekah Robert (European Scientific Journal, ESJ, 2019)
Anglophone Cameroon is the present-day NorthWest and SouthWest (English Speaking) regions of Cameroon herein referred to as No-So. These regions of Cameroon have been restive since 2016 in what is popularly referred to as the Anglophone crisis. The crisis has been transformed to a separatist movement, with some Anglophones clamoring for an independent No-So, re-baptized as “Ambazonia”. The purpose of the study is to illuminate the geopolitical perspective of the conflict which has been evaded by many scholars. Most scholarly write-ups have rather focused on the causes, course, consequences and international interventions in the crisis, with little attention to the geopolitical undertones. In terms of methodology, the paper makes use of qualitative data analysis. Unlike previous research works that link the unfolding of the crisis to Anglophone marginalization, historical and cultural difference, the findings from this paper reveals that the strategic location of No-So, the presence of resources, demographic considerations and other geopolitical parameters are proving to be responsible for the heightening of the Anglophone crisis in Cameroon and in favour of the quest for an independent Ambazonia. This article however upholds that the No-So is still part of Cameroon’s territorial space, considering the fact that Ambazonia is not internationally recognized as a sovereign state.